2015
DOI: 10.1093/treephys/tpv022
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of competition at decameter scale: patches of high canopy leaf area in a shade-intolerant larch stand transpire less yet are more sensitive to drought

Abstract: Small differences in the sensitivity of stomatal conductance to light intensity on leaf surfaces may lead to large differences in total canopy transpiration (EC) with increasing canopy leaf area (L). Typically, the increase of L would more than compensate for the decrease of transpiration per unit of leaf area (EL), resulting in concurrent increase of EC. However, highly shade-intolerant species, such as Larix principis-rupprechtii Mayr., may be so sensitive to increased shading that such compensation is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…However, L is also greatly affected by the large spatial variation in tree density and sapwood area per unit of ground area (Oren et al 1998a), reflecting local variation of resource availability, such as water and nutrients as affected by rooting volume (e.g., in relation to rock content and soil depth; McCarthy et al 2006), weatherrelated disturbances (McCarthy et al 2006, Xiong et al 2015, or management (Zhang et al 2012). Modification of site resources, such as water and nutrients, may differentially affect A S and A L , decoupling stand transpiration from L (Ewers et al 2001).…”
mentioning
confidence: 99%
“…However, L is also greatly affected by the large spatial variation in tree density and sapwood area per unit of ground area (Oren et al 1998a), reflecting local variation of resource availability, such as water and nutrients as affected by rooting volume (e.g., in relation to rock content and soil depth; McCarthy et al 2006), weatherrelated disturbances (McCarthy et al 2006, Xiong et al 2015, or management (Zhang et al 2012). Modification of site resources, such as water and nutrients, may differentially affect A S and A L , decoupling stand transpiration from L (Ewers et al 2001).…”
mentioning
confidence: 99%
“…To some extent, the LAI can reflect the total leaf area and the number of stomata (Wang et al, ). Within the low range of LAI, the evaporation surface area and stomata number increase with rising LAI, the ability of trees to transfer water from soil to leaves accordingly enhances; thus, the stand T increases (Gong et al, ); the stand T will no longer increase with rising LAI when the LAI is within the high range, this is because stomatal closure and the decrease of received light for lower leaves with increased mutual shading directly translates to a decrease of transpiration per unit of leaf area with increased LAI (Xiong et al, ). In this study, stand T with rising LAI exhibited a saturated exponential increase relation, being in line with the study of Wang et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Thus, coupling the different responses of ET components to variation of the main driving factors is required. At a given site with certain soil and landform conditions, the main factors driving the ET components can be simplified and divided into several aspects: the depth of precipitation (P) and the potential evapotranspiration (ET ref ), which reflect the effect of changing weather (Granier et al, ; Ungar et al, ); the relative extractable water (REW) or volumetric soil moisture (VSM), which reflects the water supply ability from the root zone soil layer (Lagergren & Lindroth, ; Sinclair et al, ; Ungar et al, ); and the forest canopy leaf area index (LAI), which reflects the water conveying capacity of vegetation or canopy structure (Bucci et al, ; Xiong et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In related studies, trees were distinguished by DBH, and larger trees were found to generally transpire more than smaller trees [24,26], but it was also found that the mean sap flow of trees was not strongly correlated with DBH [18,22,44]. In addition to DBH, tree dominance in forest was also the main influencing factor on transpiration [22], because it was related to the ability to acquire living resources, including water and energy resources.…”
Section: Tree Dominance Determines Its Role In Forest Transpirationmentioning
confidence: 99%